Association Between Changes in Post-hospital Cardiac Symptoms and Changes in Acute Coronary Syndrome-Induced Symptoms of Post-traumatic Stress - von Känel, Roland; Meister-Langraf, Rebecca E.; Zuccarella-Hackl, Claudia; Znoj, Hansjörg; Pazhenkottil, Aju P.; Schmid, Jean-Paul; Barth, Jürgen; Schnyder, Ulrich; Princip, Mary (Frontiers in Cardiovascular Medicine, 2022)
Background: After acute coronary syndrome (ACS), one in eight patients develops clinically significant symptoms of posttraumatic stress disorder (PTSD). We hypothesized that changes in cardiac symptoms from 3 to 12 months after ACS are associated with changes in ACS-induced PTSD symptoms. Methods: At 3 (n=154) and/or 12 months (n=106) post-ACS, patients (n=156, mean age 59 years, 85% men) completed a clinical interview assessing chest tightness/pain (at rest and/or during exertion), heartbeat symptoms (heart palpitations, racing of heart, heart stumbling or skipping a beat) and PTSD symptoms during the prior 4 weeks. Random mixed regression models examined the association between the onset (or remission) from 3 to 12 months in cardiac symptoms with changes in PTSD symptoms, adjusting for a range of potential predictors of ACS-induced PTSD symptoms. Results: The onset of chest tightness/pain [estimate =0.588, 95% confidence interval: 0.275, 0.090; p<.001] and of heartbeat symptoms [0.548 (0.165, 0.931); p=.005] from 3 to 12 months was independently associated with an increase in total PTSD symptoms. There were also independent associations between the onset of chest tightness/pain and heartbeat symptoms with an increase in PTSD symptom clusters. Specifically, the onset of chest tightness/pain showed associations with an increase in re-experiencing [0.450 (0.167, 0.733); p=.027] and avoidance/numbing [0.287 (0.001, 0.574); p=.049]. The onset of heartbeat symptoms showed associations with an increase in re-experiencing [0.392 (0.045, 0.739); p=0.002], avoidance/numbing [0.513 (0.161, 0.864); p=.004] and hyperarousal [0.355 (0.051, 0.659); p=.022]. An increase in the total number of cardiac symptoms (score range 0-6) was also associated with an increase in total PTSD symptoms [0.343 (0.202, 0.484); p<.001]. Psychotherapy in the post-hospital period moderated the association between the change in heartbeat symptoms and the change in total PTSD symptoms [-0.813 (-1.553, -0.074); p=.031 for interaction]; the association between the onset of heart beat symptoms and an increase in total PTSD symptoms was weaker in patients who attended psychotherapy [0.437 (-0.178, 1.052); p=.16] than in those who did not [0.825 (0.341, 1.309); p<.001]. Conclusions: Changes in cardiac symptoms between 3 and 12 months after hospitalization are associated with changes in ACS-induced PTSD symptoms. ClinicalTrials.gov #NCT01781247.